1978
DOI: 10.1111/j.1440-1681.1978.tb00646.x
|View full text |Cite
|
Sign up to set email alerts
|

CHOLIC ACID AND THE HEART: IN VITRO STUDIES OF THE EFFECT ON HEART RATE AND MYOCARDIAL CONTRACTILITY IN THE RAT

Abstract: 1. Cholic acid has a dose-dependent negative chronotropic effect on isolated atria of Wistar rats. 2. The positive inotropic effect of cholic acid is the result of a negative chronotropic effect and can be eliminated by electrical pacing. 3. Cholic acid does not appear to exert its negative chronotropic effect through cholinoceptors and alterations in bath concentrations of calcium and potassium does not influence this effect significantly. 4. Cholic acid is a functional antagonist of isoprenaline. 5. It is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 6 publications
(1 reference statement)
1
32
0
Order By: Relevance
“…A possible mechanism for bile acid-induced arrhythmogenesis is interaction of bile acids with the cell membrane and cell membrane ion channels or transporters 21 25 26. Bile acids are amphiphilic molecules and are negatively charged at physiologic conditions 27.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for bile acid-induced arrhythmogenesis is interaction of bile acids with the cell membrane and cell membrane ion channels or transporters 21 25 26. Bile acids are amphiphilic molecules and are negatively charged at physiologic conditions 27.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids have been shown to exert a direct depressant effect on cardiac function (Wakim et al, 1940;Joubert, 1978;Bogin et al, 1983;Green et al, 1984). Furthermore, Song et al (1983) demonstrated that sinus bradycardia is induced by obstructive jaundice.…”
Section: Introductionmentioning
confidence: 99%
“…This contrast was also observed in isolated papillary muscle contractility studies [13,27]. The existence of other cardiodepressant substances, e.g., bile acids [28,29], which are in their maximum serum concentration approximately toward the end of the first week and gradually decline with time [30], alongside with NO and endogenous opioid peptides, might be the reason why L-NAME treatment restores baseline hemodynamic parameters as well as the attenuated inotropic responses to isoproterenol in the cirrhotic rats, whereas such responses were not observed in the acute cholestatic animals. The failure of acute L-NAME administration to either correct QT c interval or restore the susceptibility to arrhythmias suggests these changes are the results of long-term overproduction of NO which cannot be reversed by acute inhibition of NO production.…”
Section: Role Of Nomentioning
confidence: 69%